Stakeholder Perceptions of Nature-Based Solutions and Their Collaborative Co-Design and Implementation Processes in Rural Mountain Areas—A Case Study From PHUSICOS - Lupp, Gerd; Huang, Joshua J.; Zingraff-Hamed, Aude; Oen, Amy; Del Sepia, Nicola; Martinelli, Alberto; Lucchesi, Massimo; Wulff Knutsen, Turid; Olsen, Mari; Fjøsne, Trine Frisli; Balaguer, Eva-Maria; Arauzo, Idoia; et al. (Frontiers in Environmental Science, 2021)
Planners and engineers increasingly discovered nature as a source of inspiration to mitigate hydro-meteorological risks resulting from extreme weather events. Actors are realizing advantages of such solutions known as Nature-Based solutions (NBS) to rapidly adapt to changing climate patterns and related impacts such as flooding, landslides, mudflows or rockfalls. NBS also provide multiple co-benefits such as an increased landscape value for society and biodiversity. Because of their inherent characteristics, NBS implementation are more efficient when supported by participative approaches. At the same time, strengthening democratic and collaborative planning into Living Labs approaches generates an increase in interest. This helps to overcome bottlenecks when implementing measures and provide common ground to provide space for new ideas, to promote innovation and to develop solutions with high acceptance. While co-design and implementing NBS has already been applied and well documented for urban areas, there are few publications on collaborative planning, stakeholder perception and NBS co-implementation in rural mountain areas. In our case study analysis from the EU-funded H2020 project PUSICOS, we present stakeholder views on NBS, their possibility to reduce natural hazards in different mountainous case study areas, different discussed measures, NBS types and stages of implementation. We analyze expectations on Living Lab processes to co-design NBS and important topics to be addressed in these processes from the view, perspective and perception of local stakeholders. These insights will help us to understand and address the management of intense stakeholder involvement processes, to identify barriers that arise, and to support in-depth participatory processes.